A Netnographic Study of Cross-Cultural Miscommunication in Digital Mental Health Nursing and Telepsychiatry Among Online Communities - Bagus Dwi Cahyono; Mareta Deka Paraswati; Domingos Soares (Tarqabin Nusantara Group, 2026)
Background: A chatbot cannot ask about a patient's family before it asks about their symptoms, and in cultures where healing begins with relationship rather than data, that single omission may be where digital psychiatric care quietly loses the people it was built to reach. Telepsychiatry and tele-nursing platforms have expanded rapidly across Southeast Asia, yet whether these tools translate psychological distress across cultural boundaries, and not merely across language, remains poorly understood. This study explored how Indonesian- and Malay-speaking internet users described experiences of cross-cultural miscommunication with digital mental health providers. Methods: A 20-week netnographic study was conducted across Indonesian- and Malay-language online communities discussing telepsychiatry, tele-nursing, and digital mental health applications. Publicly available discussion threads were analysed using an inductive, Braun-and-Clarke-informed thematic approach. Results: Analysis of threads from participants who described a personal digital mental health encounter generated four interconnected themes: linguistic and semantic dissonance, relational asymmetry and digital etiquette mismatches, algorithmic cultural bias in screening, and an anonymity–trust paradox. Conclusion: Cultural miscommunication in digital psychiatric nursing appears to cluster around the translation of idioms of distress and the compression of relational care into transactional data collection. Culturally responsive intake design and provider training may help narrow this gap, although the findings warrant confirmation in structured, representative samples.